Coexistence of situs inversus totalis and hepatocellular carcinoma: A series of nine cases and a literature review - Xiaowei Li; Zhigang Fu; Jiaming Zhong; Kunkun Cao; Xiaoxia Chen; Ning Ding; Li Liu; Jian Zhai; Zengqiang Qu (Journal of Interventional Medicine, 2022)
Hepatocellular carcinoma (HCC) is the most commonly diagnosed carcinoma and one of the leading causes of cancer-related deaths worldwide. Situs inversus totalis (SIT) is a congenital condition where in the internal organs of the abdomen and thorax lie in mirror images of their normal position. Thus far, there are very few reports on cases of SIT coexisting with HCC. Our case series is probably the largest series in world literature. The cohort of this retrospective study included a total of nine patients diagnosed with SIT-HCC and treated in our hospital between January 2013 and May 2018. Clinical characteristics, prognostic factors, and outcomes were summarized. Treatment strategies included surgery, transarterial chemoembolization, and microwave ablation. The diagnosis and treatment of patients with SIT are challenging because of organ reversion. The current treatment strategies for different stages of liver cancer are safe and feasible for patients with SIT-HCC.